Writing Today: Contexts and Options for the Real World - Pharr Donald (McGraw -Hill, 2004)
As composition ontructors with sixty years of experience between us, we have learned that today’s college student need and want a curriculum that challenges them in the classroom, provides them with skill they can use in other college course, and, most important, prepares them to communicate effectively in the professional and business words. Our goal in Wringting Today is to give student realistic, practical reason to master college reading and wringting because success in wringting is a prerequisite achieving continued success in college and in their career. Therefore, we dicideed to write a text that would on both academic and professional contexts for wringting. Throughout Wringting Today, we dediberately address the skepticism of student who see English composition classes as just another hurdle on their way to a degree. Wringting Today helps them use reading and wringting as tools for continued intellectual growth that they can employ in any wringting context they confront, long after having completed even their most advanced degrees.